2022
DOI: 10.1111/nicc.12744
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and burnout in critical care nurses: A cross‐sectional descriptive study

Abstract: Background Employee bullying and burnout are two crucial, prevalent and challenging concepts that adversely affect organizational staff behaviours. Also, adverse patient care is associated with nurse bullying and burnout. Aim This study aimed to assess the incidence and association between workplace bullying and occupational burnout among nurses in critical care units in Iran. Study design A cross‐sectional descriptive study. Methods The subjects were 184 nurses from critical care units in 6 teaching hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
6
1
1
Order By: Relevance
“…When compared to a previous study, [23][24][25] it was discovered that there is an increasing trend in severities for all three domains of burnout, with lack of personal accomplishment increasing by more than 50%, emotional exhaustion increasing by more than 30%, and depersonalization increasing by 40%.…”
Section: Discussioncontrasting
confidence: 57%
“…When compared to a previous study, [23][24][25] it was discovered that there is an increasing trend in severities for all three domains of burnout, with lack of personal accomplishment increasing by more than 50%, emotional exhaustion increasing by more than 30%, and depersonalization increasing by 40%.…”
Section: Discussioncontrasting
confidence: 57%
“…As such, this area of study is essential in critical care nursing settings where reported rates of bullying are high 8 . Examining this area, Amini et al's 9 study from Iran showed a positive relationship between workplace bullying and occupational burnout syndrome and highlighted concerning levels of both experiences (respectively 75.5% and >70%) amongst participants. Flexibility, understanding and involving nurses in their work assignments were recognized as important in reducing the potential for burnout.…”
Section: Workplace Environmentmentioning
confidence: 99%
“…With time and due to the stress generated from such conflict, faculty members might perform counterproductive work behaviors toward their colleagues and/or institutions as a symptom of job burnout (Kazemi et al, 2022). A study by Amini et al (2023) found that burnout is significantly correlated with workplace bullying. Another study by Esbati and Korunka (2021), who studied different levels of organizational conflict, including intergroup conflict and intragroup conflict, found a relationship between burnout and those types of conflict.…”
Section: Workplace Conflictmentioning
confidence: 99%